Aplikasi Ijma’ dalam Praktik Ekonomi Syari’ah - Zainil Ghulam (IQTISHODUNA: Jurnal Ekonomi Islam, 2018)
Nowdays, the development of sharia economic and financial business in Indonesia has transformed not only in economic practice and concept but also to take a role and lead all arroud economic sectors of Indonesia. Thus, sharia economic and financial business can become a major player for the next time. Ijma>' is one of the source of legal foundation in Islam, so ijma>' is a part of source of standard for the development of sharia economic. Studies on the application of some sources (masdar) of Islamic law such as qiyas, istihsan, istishab etc., in the practice of sharia economic is practically little. Of course, this is important because it can help the sharia economic actors to keep all sharia products are according to the Islamic Sharia.